(untitled) (Pubmet, 2023)
Open science, accessibility and knowledge sharing, especially of articles and monographs resulting from publicly funded research, seem to be a positive direction in the development of science and have received almost unanimous approval from the scientific community. However, when it comes to data sharing, voices are not in unison. Concerning natural sciences, the data collected could become completely anonymised, while the anonymisation of data in Social Science and Humanities, e.g. ethnology and anthropology, could still result in recognisability of interlocutors. Anthropologists and ethnologists have been using qualitative methodological tools since the inception of the discipline, documenting their research and data collected (audio tapes, transcripts, diaries, drawings, video tapes). However the data collected were never kept in an open-source archive. On the other hand, historians “discovered” classical anthropological methodology, interviewing people of interest (recording in-depths interviews and transcribing) and applied it to, at least for them, a new type of source - people that witnessed some important (or even not so important) historical events (Dunaway and Baum 1984). They moved a step further because, unlike anthropologists, they wanted to make this source (in the shape of an edited transcript and audio file) accessible to other researchers. They have set up Oral history and Oral history archives that have now been in existence for more than half a century (Starr 1996 (1984): 40) and have started contributing to current goals of open science quite early. A standard procedure in conducting an in-depth interview (as the most common qualitative methodological tool for anthropology (today mostly anthropology by appointment (Hannerz 2006)) is providing enough information for the interlocutor in order to sign an informed consent. Apart from describing the research, the informed consent sheet has to contain data explaining the procedure of keeping and managing the data, as well as mentioning the media in which the data will be presented (articles, exhibitions, documentaries, etc.). Anonymity is always one of the possibilities informed consent offers, and while most interlocutors opt for it, not all do. Occasionally, the interlocutor insists on periodically switching off the recorder by the researcher, usually when something delicate is being recollected. Interlocutors are aware that their voices can be recognized and try to make sure that this does not happen. Also, quite often, after the interview ends, the researcher can hear the information that was not meant to be recorded. Although there are ways to anonymise the data (as explained in Celjak, et al. 2020), interlocutors coming from smaller communities or groups can be recognized from the parts of the transcript that have not been removed (to secure anonymity) or by voice. Also, the obligation of the researcher to describe the ways in which the data will be managed in the future will inevitably impact the narratives collected. Anthropologists have already noticed the difference between “order imagined” and the “order realized” (e.g., the ideal wedding vs. actual wedding traditions). One must consider that the possibility to share, for example, their wedding story with future researchers (whoever they may be), might, for some, result in the creation of a narrative with future researchers in mind - a sort of ‘FAIRy Tale’ for the future. After all, imagine yourself recollecting your own wedding to a researcher, but also knowing that it will become a story for the archive or repository? What kind of story would you tell? And what if we are researching certain delicate topics, such as in vitro fertilization (IVF) experiences or the experience of individuals working stigmatized jobs? Having all that in mind I argue for a more vigilant approach of agencies funding research when embracing the idea that all data should be available. Not all data should be made available because this could, in the end, compromise the integrity of the research process. Some data must remain in the space of trust created between main actors in the research process.